The Effect Of Training, Compensation And Organizational Culture On The Performance Of Production Division Employees With Job Satisfaction Mediation At Pinehill Arabia Food Limited, Jeddah Saudi Arabia - Ruhyat Azhari; Dewi Yustiana; Sari Handayani; Ahmad Zainuddin; Trenggono Sumunu (PT Maju Malaqbi Makkarana, 2026)
This study aims to analyze the effect of training, compensation, and organizational culture on employee performance Pinehill Arabia Food Limited, either directly or through job satisfaction as a mediating variable. The population of this study is all employees of Pinehill Arabia Food Limited as many as 89 people, and all members of the population were sampled through the census method because the number of employees is relatively small and easy to reach. The Data were analyzed using Partial Least Square (PLS) approach with the help of Smart PLS 3.0. The results showed that training, compensation, and organizational culture have a positive and significant effect on employee performance, which is indicated by the value of each: training can contribute to improving employee performance (③ = 0.454; T = 5.440; p = 0.000), compensation can contribute to improving employee performance (③ = 0.393; T = 4.820; p = 0.000), organizational culture can contribute to improving employee performance (③ = 0.202; T = 2.376; P = 0.018), on the indirect path, job satisfaction was shown to mediate the relationship of training to performance (⑧=0.110; T = 1.967; p = 0.050) and compensation to performance (⑧=0.136; T = 2.362; p = 0.019). However, job satisfaction did not mediate the relationship of organizational culture to performance (⑧= 0.060; T = 1.302; p = 0.194).These findings confirm that improving the quality of training, equitable compensation, as well as strengthening the organizational culture of employees contribute directly to improving performance. In addition, job satisfaction acts as an important mechanism in strengthening the influence of training and compensation on performance. This study provides implications for companies to prioritize human resource development through strategic training and compensation policies.